RATIFYING THE WTO AGREEMENT ON FISHERIES SUBSIDIES: THE CHALLENGES AND OPPORTUNITIES FOR INDONESIA - Firmansyah, Jenny Khalila; Wardah, Wardah (Universitas Syiah Kuala, 2025)
Indonesia, as the worlds second-largest seafood producer, faces significant challenges in managing fisheries subsidies due to their contribution to overfishing, Illegal, Unreported, and Unregulated (IUU) fishing, and marine resource depletion. This study employs a normative legal research methodology, examining primary legal sources such as the WTO Agreement on Fisheries Subsidies (AFS), Law No. 7 of 2016 on the Protection of Fishermen, Fish Farmers, and Salt Farmers, and related regulations, complemented by secondary literature and semi-structured interviews with relevant government officials. The analysis compares Indonesias legal provisions with AFS requirements, identifying partial compliance and gaps in transparency, sustainability criteria, explicit prohibitions on harmful subsidies, and enforcement mechanisms. Findings also reveal weaknesses in Monitoring, Control, and Surveillance (MCS) systems, data collection, and equitable subsidy distribution. To address these issues, the paper proposes targeted legal amendments, technology-driven data reporting, phased subsidy reforms that safeguard small-scale fishers livelihoods, and strengthened regional cooperation through ASEAN frameworks. Ratifying the AFS, if paired with these reforms, would enable Indonesia to fulfil its international obligations while advancing sustainable fisheries governance.